Pengaruh Metode Modelling The Way Anekdot Pada Siswa Kelas X SMA Swasta Pembangunan Galang - Nur Aisyah Apriani Rambe; Azar Umar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research was motivated by the low ability of students to write anecdotal texts which was influenced by several factors. This research aims to determine the effect of the way modeling method on the ability to write anecdotal texts by class X students of Galang Development Private High School. The population in this study were all class X students of Galang Development Private High School, namely 56 people. The samples in this study were 28 students in class X IPA 1, and 28 students in class X IPS 1. The method used in this research is an experimental method using a Two Group Posttest Design. Data analysis techniques use analysis requirements tests, normality tests, and hypothesis tests. The results in the experimental class obtained an average of 72.46 in the good category, while the research results in the control class obtained an average of 66.35 in the sufficient category. Based on the similarity test of the average score of the experimental class and the average score of the control class, it is known that the results of the ability to write persuasive texts for the two groups show significant differences. The results of hypothesis testing with the